A new species of Bruchomyiinae (Diptera: Psychodidae) from Baltic amber - Skibińska, Kornelia; Szadziewski, Ryszard; Kania, Iwona; Krzemiński, Wiesław (Zootaxa, 2020)
Bruchomyiinae is one of seven subfamilies of Psychodidae. This small group comprises fewer than 60 extant species distributed mainly in tropical and sub-tropical regions (Wagner & Stuckenberg 2016). All life stages of these flies are closely tied to forest environment (Fairchild 1952; Stuckenberg 1962) and as a result, bruchomyiines are frequently preserved in fossil resins. The first fossil member of this subfamily was described from Baltic amber (45 Ma) (Meunier 1905) and Burmese amber (100 Ma) is the oldest fossil resin in which representatives of Bruchomyiinae have been found (Stebner et al. 2015; Wagner 2017; Skibińska et al. 2019). Due to the relative scarcity of this subfamily in Baltic amber, any new specimens are of great interest. Up till now, there are only 12 bruchomyiine species described from Baltic amber. Wagner (2017) completed a revision of fossil Bruchomyiinae and proposed the genus Hoffeinsodes to include the species having male genitalia with gonocoxites fused with hypandrium. In this genus, he classified six species reported exclusively from Eocene Baltic amber: H. bifida Wagner, 2017, H. cubicula Wagner, 2017, H. longicauda Wagner, 2017, H. obtusa Wagner, 2017, H. reducta Wagner, 2017 and H. hoffeinsi (Wagner, 2006) transferred from Nemopalpus (Wagner, 2006). Here, we describe a new species belonging to this genus.